2014
DOI: 10.1177/1087057114536227
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High-Throughput Screening of Natural Product Extracts to Identify Proapoptotic Inhibitors of Bcl-2 Family Proteins

Abstract: Antiapoptotic Bcl-2 family proteins are validated cancer targets composed of six related proteins. From a drug discovery perspective, these are challenging targets that exert their cellular functions through protein-protein interactions (PPIs). Although several isoform-selective inhibitors have been developed using structure-based design or high-throughput screening (HTS) of synthetic chemical libraries, no large-scale screen of natural product collections has been reported. A competitive displacement fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Such an FP assay also provides an opportunity for the detection of inhibitors targeting the PPI . For instance, an FP competition assay has been developed to identify inhibitors targeting the MDM2–p53 peptide interaction, to screen small molecules that inhibit the ZipA–FtsZ peptide interaction, to screen natural product extracts that disrupt the binding of antiapoptotic Bcl‐2 family members to Bim BH3 peptides . The advantages of an FP assay are its low cost, simple mix‐and‐read format without wash steps, and the high‐throughput screening (HTS) capacity of the assay when carried out in a multiwell plate (96/384/1,536).…”
Section: Biophysical Methodsmentioning
confidence: 99%
“…Such an FP assay also provides an opportunity for the detection of inhibitors targeting the PPI . For instance, an FP competition assay has been developed to identify inhibitors targeting the MDM2–p53 peptide interaction, to screen small molecules that inhibit the ZipA–FtsZ peptide interaction, to screen natural product extracts that disrupt the binding of antiapoptotic Bcl‐2 family members to Bim BH3 peptides . The advantages of an FP assay are its low cost, simple mix‐and‐read format without wash steps, and the high‐throughput screening (HTS) capacity of the assay when carried out in a multiwell plate (96/384/1,536).…”
Section: Biophysical Methodsmentioning
confidence: 99%
“…It is essential to inhibit undesired PPIs in drug development, and bioactivity-guided isolation using the inhibitory activity of PPIs is an attractive method to obtain effective inhibitors. However, currently there are only a few examples of such approaches using PPI assay systems 22,23 . We previously developed a Hes1-Hes1 interaction fluorescent plate assay and reported the screening results of our natural products compound library ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent paper, a multidisciplinary group from academia and the NCI demonstrated that such a screening program was successful in identifying natural product extracts and subsequently purified natural products from the initial hits that interfered with some of the apoptotic Bcl-2 proteins [142]. In a recent paper, a multidisciplinary group from academia and the NCI demonstrated that such a screening program was successful in identifying natural product extracts and subsequently purified natural products from the initial hits that interfered with some of the apoptotic Bcl-2 proteins [142].…”
Section: Screening Methodsmentioning
confidence: 99%
“…Thus, by use of sophisticated robotic systems using in vitro and in cellulo assays, Hassig et al were able to identify novel agents from an initial screen of close to 150,000 crude extracts from plants, microbes, and marine invertebrates [142]. In addition, secondary assays in a dose response format, including counter screens, both using in cellulo systems in 384 well plates and volumes of about 30 µl, were also necessary in order to confirm that results observed in the in vitro conditions could occur within the cell (transfer across membranes, etc.).…”
Section: Screening Methodsmentioning
confidence: 99%